Behavioural preference for Google and ChatGPT in an online search task. - Healy, Kylee; Radell, Milen L. (Behaviour & Information Technology, 2026)
The advent of readily accessible Artificial Intelligence (AI) platforms, such as ChatGPT, has increased uncertainty, and in education, raised concerns about plagiarism and other negative behaviours. Most previous research, however, has relied on self-report to measure student use of AI, rather than observing actual behaviour. This preregistered study compared how 55 college students use a traditional internet search platform (Google) to how they use AI (ChatGPT) to complete an online search task with well- and ill-defined questions. Additionally, it examined whether preference was related to personality traits indicative of the tendency to explore novel experiences, including intolerance of uncertainty and personal expansion. It was hypothesised that students will prefer to use Google over ChatGPT, in particular when they are more intolerant of uncertainty. Contrary to this hypothesis, significantly more participants preferred to use ChatGPT, but only for the ill-defined question. There was no preference when responding to the well-defined questions, and no evidence that personality or previous experience with the platforms were related to preference. However, students with higher intolerance of uncertainty were more likely to have used ChatGPT in the past, suggesting that this trait may help predict the tendency to learn about and use new technology.